Evaluation of pregnancy induced receptor pathway of programmed cell death of renal tubular epithelial cells - Pedrycz, Agnieszka; Zając, Grzegorz; Zwierzyński, Mariusz; Zając, Agata (Current Problems of Psychiatry, 2025)
The aim of this study was immunohistochemical evaluation of extrinsic pathway of apoptosis in renal epithelial cells in pregnant rats including time. We evaluated in immunohistochemical way expression of caspase 8 – activated in receptor’ s pathway. Rats used in this experiment was divided into 4 groups – 8 individuals each: I group – female rats which was fertilized and decapitated in 10 day of pregnancy, II group female rats which was fertilized and decapitated in 20 day of pregnancy III group female rats which was fertilized and decapitated in 10 day after delivery VI group – control – female rats which decapitated in 30 day of experiment. Specimens of kidneys taken to examine we analyzed in immunohistochemical standard three-step method detecting caspse8 protein. Immunohistochemical positive reaction increased in all experimental groups compared to control. There was no significant differences between groups examined in 10 day of pregnancy and in 10 day after delivery. Pregnancy induced hormonal changes activated apoptosis by induction of extrinsic pathway by activation of caspase 8 manly on the and of pregnancy (20th day of pregnacy). Extrinsic pathway was induced in 10 day of pregnancy on the same level like 10 days after delivery. This level was lower than in 20day of pregnancy.